Національна історико-культурна спадщина в системі історичної пам’яті та викликів сучасної глобалізації - Барановська, Н. М. (Lviv Polytechnic Publishing House, 2016)
Теоретично обґрунтувано соціогуманітарні трансформації, їхні загрози та можливості у сучасних глобалізаційних умовах розвитку українського суспільства. Увагу закцентовано на ролі та значенні національної історико-культурної спадщини для формування консолідаційного потенціалу об’єктивної історичної пам’яті та її використанні у культурно-пізнавальній сфері й міжнародній діяльності. З’ясовано роль історичних музеїв як важливих пам’яткоохоронних і дослідницьких установ у системі суспільних цінностей та змістовного наповнення національної ідеї. Встановлено загальні чинники, які впливають на формування національної ідентичності в межах глобального світосприйняття. The article is devoted to theoretical substantiation of sociohumanitarian transformations, their threats and opportunities in modern globalizational conditions of Ukrainian society’s development. Attention is paid to the role and significance of national historical and cultural heritage to form consolidational potential of objective historical memory and its use in cultural and educational sphere and international activity. The role of museums as important institutions for protection of monuments and research activity in the system of social values and rich in content filling of the national idea is clarified.The general factors that affect the formation of national identity within the global world-view are identified. Globalization and related challenges in recent years are the subject of active research in scientific community. Carrying the popular idea of integration readiness, globalization entails unification of history, pulls aside from the real impact on national development, politics and culture of historical memory. Management of historical consciousness becomes prominent. Inspiring and traumatic moments of the historical memory that in the past were causing contradictions and conflicts are becoming not important. They are displayed in a shadow or activated in accordance with the objectives of political expediency. This primarily relates to periods of liberation struggle of Ukrainian people for statehood revival that changed the political situation in Ukraine within the national paradigm, evaluation of prominent historical figures activity, because of which there are sometimes ideological disputes about controversy questions of SecondWorld War, historical memory about the state terror of the Soviet totalitarian regime (20–50’s XX century), the victims of which were millions of Ukrainian. An effective counterweight to globalizational processes, that threaten the information security of Ukraine may be renewal of society’s interest to national historical and cultural heritage as a valuable intellectual property of the Ukrainian nation, powerful mean of national self-identification, consolidation and formation of objective historical memory. An important role in processes of preservation, study and actualization of historical and cultural heritage belongs to the Historical Museum. Modern information technology and socio-cultural changes create new opportunities for effective transformation of historical and cultural values into museum exibits, rethinking of the museum displays towards rich in content filling of the national idea. This activity will help to prevent the growing trend towards cultural unification by forming in the minds of the Ukrainian nation’s representatives a sense of its unique history, culture and struggle for statehood. In addition, the value of national achievements should be meaningfully and interestingly revealed to the world, making them more prominent, featuring Ukrainian heritage as an integral and distinctive part of the historical and cultural heritage of humanity. This may be one of the most effective means to draw attention of the international community to the problem of necessity to maintain national sovereignty and territorial integrity of Ukraine in threatening her present conditions.
Keywords: глобалізація; виклики; об’єктивна історична пам’ять; історико-культурна спадщина; історичний музей; самобутність; globalization; challenges; objective historical memory; historical and cultural heritage; historical museum; originality; 930.8:005.44